Implementation of Augmented Reality in Animal Introduction Learning for Students with Intellectual Disabilities - Pangestu, Yoga; Wulandari, Sri; Handayani, Irma (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Introducing animals and their characteristics to mentally disabled students is a complicated matter. Mental retardation is a condition where a person's intellectual and cognitive intelligence is below average, which causes limitations in thinking, solving problems, remembering, and easily losing focus. Because of this, mentally disabled students develop more slowly than normal children their age. To help overcome developmental delays and improve their memory, special treatment and education are needed that suit their needs. Schools can utilize Augmented Reality (AR) technology as an alternative educational tool to make the teaching and learning process at school more fun, interesting and interactive so that it can leave a deep impression on students. This research aims to design and build an application to introduce animals by applying augmented reality technology. This research uses the Multimedia Development Life Cycle (MDLC) method; in this method, there are six stages: concept, design, material collection, design, testing, and distribution, with the testing method using black box testing. This research results in an Android-based augmented reality application for animal recognition for mentally disabled students. This application can make the teaching and learning process more interesting and enjoyable for students and make it easier for teachers to introduce animals and their characteristics.